Implementation of robust multi-objective optimization in the build orientation problem - Matos, Marina A. (2021)
Additive manufacturing (AM) is an emerging technology to create 3D objects layer-by-layer directly from a 3D CAD model. The build orientation is a critical issue in AM and its optimization will significantly reduce the building costs and improve object accuracy. This paper aims to optimize the build orientation problem of a 3D CAD model using a robust multi-objective approach, taking into account the staircase effect and the support area characteristics. Thus, themain objective is to obtain a robust Pareto optimal front, composed of solutions that are not quite sensitive to perturbations in the variables. In this manner, a set of robust solutions is presented as alternatives and the decision-maker can identify the compromise solutions and choose according to his/her preferences.